Scottish oaths
Oath (circa 1752) required of Scots by the government of Great Britain against carrying weapons or wearing highland garb; and oath of allegiance (1910) to George V, King of Great Britain.
Typewritten transcripts.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: George -- V, -- King of Great Britain, -- 1865-1936.; Costume -- Scotland; Oaths -- Scotland; Weapons -- Scotland; Scotland -- History